An introduction to metallurgy - Cottrell, Alan, 1919-2012 (Institute of Materials, 1995)
This classic textbook has been reprinted to provide undergraduates with a broad overview of metallurgy from atomic theory, thermodynamics, reaction kinetics and crystal physics, to elasticity and plasticity.
Originally pubd.: London : Edward Arnold, 1975.
Keywords: Metallurgy.; elektronické knihy; electronic books